Clinicopathological relevance of stem cell marker growth and differentiation factor 3 in esophageal squamous cell carcinoma - Sara Tahbazzadeh Moghaddam; Mohammad Mahdi Forghanifard (Open Exploration Publishing Inc., 2023)
Esophageal squamous cell carcinoma (ESCC) is the second leading cause of cancer-related deaths in Iran, often diagnosed in advanced stages with a poor prognosis. Growth and differentiation factor 3 (GDF3) is a member of the transforming growth factor-beta (TGF-β) superfamily. It acts as an inhibitor of bone morphogenetic proteins (BMPs) signaling pathway associated with pluripotent embryonic and cancer stem cells (CSCs) characteristics. Since its expression in ESCC has not yet been evaluated, the clinicopathological relevance of GDF3 expression was elucidated in ESCC patients. Expression of GDF3 in tumor tissues from 40 ESCC patients was compared to the related margin normal tissues by relatively comparative real-time polymerase chain reaction (PCR). Glyceraldehydes 3-phosphate dehydrogenase (GAPDH) was used as the endogenous control. Likewise, the function of GDF3 in the differentiation and development of embryonic stem cells (ESCs) was also reviewed. GDF3 was significantly overexpressed in 17.5% of tumors and a significant correlation between GDF3 expression and the depth of tumor invasion was observed (P = 0.032). The results suggest that GDF3 expression is likely to have substantial roles in the progression and invasiveness behavior of ESCC. Having considered the importance of CSC markers identification and their exploitation in targeted cancer therapy, GDF3 may be introduced as a promising therapeutic target to inhibit the invasion of tumor cells in ESCC.